Case Report: Initial Treatment Adjustments and Complications in Ovarian Cancer Patient With Inborn Error of Immunity - Mammadova, Jamila; Redden, Anna; Cruz, Rachel; Ujhazi, Boglarka; Gordon, Sumai; Ellison, Maryssa; Gatewood, Tyra; Duff, Carla; Cannella, Anthony; Somboonwit, Charurut; Sriaroon, Chakrapol; Csomos, Krisztian; et al. (Frontiers in Oncology, 2022)
Background Patients with inborn errors of immunity (IEI) have increased risk of developing cancers secondary to impaired anti-tumor immunity. Treatment of patients with IEI and cancer is challenging as chemotherapy can exacerbate infectious susceptibility. However, the literature on optimal cancer treatment in the setting of IEI is sparse. Objectives We present a patient with specific antibody deficiency with normal immunoglobins (SADNI), immune dysregulation (ID), and stage III ovarian carcinoma as an example of the need to modify conventional treatment in the context of malignancy, IEI, and ongoing infections. Methods This is a retrospective chart review of the patient’s clinical manifestations, laboratory evaluation and treatment course. Results Our patient is a female with SADNI and ID diagnosed with stage III ovarian carcinoma at 60 years of age. Her ID accounted for antinuclear antibody positive (ANA+) mixed connective tissue diseases, polyarthralgia, autoimmune neutropenia, asthma, autoimmune thyroiditis, and Celiac disease. Due to the lack of precedent in the literature, her treatment was modified with continuous input from infectious disease, allergy/immunology and oncology specialist using a multidisciplinary approach. The patient completed debulking surgery and 6 cycles of chemotherapy. The dosing for immunoglobulin replacement therapy was increased for prophylaxis. Chemotherapy doses were lowered for all cycles preemptively for IEI. The therapy included carboplatin, paclitaxel, bevacizumab, and pegfilgrastim. The patient completed six-months of maintenance medication involving bevacizumab. Her treatment course was complicated by Mycobacterium avium-complex (MAC) infection, elevated bilirubin and liver enzymes attributed to excessive immunoglobulin replacement therapy, and urinary tract infection (UTI) and incontinence. Cancer genetic analysis revealed no targetable markers and primary immunodeficiency gene panel of 407 genes by Invitae was unrevealing. Lab tests revealed no evidence of Epstein-Barr Virus (EBV) infection. Post-chemotherapy imaging revealed no evidence of cancer for 1 year and 4 months, but the disease relapsed subsequently. The patient’s lung scarring requires vigilance. Conclusions Our patient with ovarian cancer and IEI required modified treatment and prevention of complications. In cases of IEI, optimal chemotherapy should be titrated to minimize immunosuppression yet treat cancer aggressively while decreasing the risk of infection with prophylactic antibiotics and prolonged post-treatment surveillance, including pulmonary evaluation.